THE INFLUENCE OF OCCUPATIONAL HEALTH AND SAFETY (OHS) ON EMPLOYEE PERFORMANCE THROUGH WORK DISCIPLINE AMONG TECHNICAL EMPLOYEES - Ahmad Amilin Faylasuuf Farosa; Muhammad Husain (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
The increasing number of workplace accidents and declining performance levels in the technician division of transportation service companies, as evidenced by reduced task completion responsibility, insufficient adherence to operational procedures and work discipline, and inconsistent utilization of personal protective equipment (PPE). This condition is reinforced by inadequate implementation of Occupational Health and Safety (OHS) standards, which has the potential to compromise employee productivity and overall work performance. Therefore, the objective of this research is to analyze the influence of OHS on employee performance, both directly and indirectly through work discipline as a mediating variable. This study applies a quantitative approach with a survey method, utilizing proportionate stratified random sampling, involving 169 technician employees selected based on the Krejcie and Morgan sample size determination table. Data were obtained through a structured Likert-scale questionnaire and analyzed using the Structural Equation Modeling (SEM) technique with the SmartPLS 3.2.9 application. The research findings demonstrate that OHS exerts a positive and significant effect on employee performance, OHS has a positive and significant effect on work discipline, and work discipline positively and significantly influences employee performance. Additionally, the results confirm that work discipline functions as a mediating variable in the relationship between OHS and employee performance. These empirical findings substantiate the importance of effective OHS implementation in fostering a safe and conducive work environment, strengthening employee discipline, and enhancing productivity and performance outcomes. This research provides theoretical contributions by reinforcing empirical literature on the mediating role of discipline within workplace safety contexts, and practical contributions by offering strategic recommendations for organizations in optimizing OHS policies, reinforcing disciplinary mechanisms, and improving employee performance management.